Document Co-citation Analysis using Concept Lattice - Gupta, Anamika; Gupta, Shikha; Bisht, Mukul; Hooda, Prestha; Salik, Md (Engineering, Technology & Applied Science Research, 2023)
Document Co-citation Analysis (DCA) is a method to identify and analyze the relationships between co-cited documents. In this paper, we attempt to use concept lattice for DCA. Concept lattice is a graph structure given in Formal Concept Analysis (FCA), a branch of mathematics based on the concept and its hierarchy. The experiments are conducted on an extensive repository of citations extracted from DBLP, ACM, MAG (Microsoft Academic Graph), and other sources, having a total of 5,354,309 papers and 48,227,950 citation relationships. In this paper, it is established that the concept lattice supports DCA and helps to identify a set of co-cited documents and their co-citation strength. It also provides navigation to reflect the subset-superset relationship of the co-citations. Further, the concept lattice helps identify the hierarchy among the documents and answers the most relevant queries related to DCA.